Leveraging Academic Performance through Technology Utilization in Mathematics Education - , Sunshine P. Infante; , Sionamie P. Abobo; , Cristine T. Crisologo (Archives of Current Research International, 2025)
Aims: This study examines the effective integration of digital tools in mathematics education to enhance students’ academic performance, engagement, and problem-solving skills. It evaluates instructional strategies, identifies challenges, and proposes solutions to improve technology implementation in teaching practices. Study Design: A mixed-method approach was employed, combining qualitative and quantitative data collection. Interviews and observations provided insights into educators' experiences, while surveys measured the frequency and effectiveness of technology usage in instruction. Place and Duration of Study: Conducted at the University of Eastern Philippines, Laoang Campus, during the 2024–2025 academic year. Methodology: Six mathematics teachers were selected through purposive sampling to ensure the inclusion of educators facing challenges in integrating technology into their teaching. Data collection involved semi-structured interviews and surveys, with thematic analysis applied to qualitative data and descriptive statistics used for quantitative responses. Results: Educators utilized diverse digital tools—including PowerPoint, GeoGebra, SPSS, HTML, Desmos, and PhotoMath to enhance lesson structure, data analysis, and interactive learning. Devices such as laptops, mobile phones, and smart TVs improved accessibility, yet challenges such as infrastructure limitations, digital literacy gaps, and student access disparities hinder full integration. Teachers addressed these barriers through strategic technology use, collaboration, and digital literacy initiatives. Conclusion: While digital tools enhance mathematics instruction, infrastructure limitations, resource accessibility, and pedagogical constraints remain obstacles. Addressing these challenges requires sustained institutional support, improved digital infrastructure, and continuous professional development. By refining teaching strategies and fostering collaboration, educators can create inclusive and technology-driven learning environments that promote student engagement, comprehension, and academic success.